DAMPAK FENOMENA JUDI ONLINE PADA PENGELOLAAN KEUANGAN INDIVIDU ( STUDI KASUS DI WILAYAH CIUMBULEUIT BANDUNG ) - Ageng saepudin kanda S; Rochmat sopiansyah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstract. This research aims to examine the impact of the rise of online gambling among society, with a focus on individual financial management. Through questionnaires and interviews with 40 respondents, the results show that there are more active online gambling players than non-players, and significant financial losses can occur. The majority of online gambling players are men. Interviews show that the main reason people engage in online gambling is the desire to gain instant profits. Negative impacts involve extravagance, hard-to-control addictions, money lending, and mental health impacts such as stress. Factors causing people to fall into online gambling involve economic pressure and environmental influences, especially through the spread of information by word of mouth and social media advertising. Significant losses can reach tens of millions, and the risk of losing money significantly increases. The research results suggest the need to increase public education, develop prevention programs, support mental health, and strengthen regulations and sanctions. Community leaders need to be actively involved in providing support, while more stable economic alternatives also need to be developed. The implications of these findings support the need for greater awareness regarding the risks of online gambling and joint efforts to protect people's financial well-being.